2017
DOI: 10.1111/tct.12590
|View full text |Cite
|
Sign up to set email alerts
|

Texting preferences in a Paediatric residency

Abstract: Forty-one residents enrolled and 32 (78%) completed a post-programme survey. Of those, 21 (66%) preferred a Q&A format with an immediate text response versus information-only texts. The percentage change in ITE scores between 2013 and 2014 was significant. Comparing subgroups, there was no significant difference between the percentage change in ITE scores. Neither group performed significantly better on either the adolescent or developmental sections of the ITE. Text messaging… remains an underused educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Residents stated that timing and frequency of learning was important, with participants preferring paced learning and incorporation of efforts early in training. A study on a text-based question and answer exam preparation platform showed that one of the positives features according to participants was that the program gave daily content and employed a rich question/answer format [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Residents stated that timing and frequency of learning was important, with participants preferring paced learning and incorporation of efforts early in training. A study on a text-based question and answer exam preparation platform showed that one of the positives features according to participants was that the program gave daily content and employed a rich question/answer format [9].…”
Section: Discussionmentioning
confidence: 99%
“…In one intervention, answering weekly questions delivered through email was correlated with better ABP CE performance results [3]. Similarly, a texting program which delivered a combination of commonly tested facts and questions to pediatrics residents was associated with improvements in their In-Training Exam (ITE) results [9]. Another residency program used a board review course method for pediatric residents who were at risk of failing the boards and described positive results with this intervention [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2011 randomised trial in China compared text messaging with a traditional lecture or workshop for improving medical knowledge, and showed a benefit in the texting group . In graduate medical education, separate texting studies with family medicine residents and paediatric residents failed to show any improvement in medical knowledge . A 2012 study with obstetrics and gynaecology (OB/GYN) residents showed an improvement in medical knowledge using a texting educational program .…”
Section: Introductionmentioning
confidence: 99%
“…W e note with interest the article by Draper et al regarding the use of texting as a learning aid. 1 As fourth-year medical students, we have devised a system of examination revision through text messaging in recognition of the utility of short pieces of information in improving recall. 2 We used the 'WhatsApp' application owing to its 'bookmark' feature, which allows users to highlight and store messages for easy retrieval.…”
mentioning
confidence: 99%